1 + 1 2 + 1 4 1 + 1 + 2 2 + 2 4 2 + 1 + 3 2 + 3 4 3 + ⋯ + 1 + 9 9 2 + 9 9 4 9 9
The value of the expression above lies between which of the following pairs of numbers?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Partial fractioning these rational functions often creates a telescoping which makes results transparent. Heaviside's method can compute numerators quickly, especially for unrepeated linear factors.
Let us take: x 4 + x 2 + 1 = ( x 2 + x + 1 ) ( x 2 − x + 1 )
Using this the above expression can be reduced into = 1 . 3 1 + 3 . 7 2 + 7 . 1 3 3 ..................................................... 9 7 0 3 . 9 9 0 1 9 9 )
Taking 2 1 common from each term = 2 1 [1- 3 1 ]+ 2 1 [ 3 1 - 7 1 ]+ 2 1 [ 7 1 - 1 3 1 ]................................................ 2 1 [ 9 7 0 3 1 - 9 9 0 1 1 ]
= 2 1 [1- 3 1 + 3 1 - 7 1 +.................................................... 9 7 0 3 1 - 9 9 0 1 1 ] = 9 9 0 1 4 5 0 0
Problem Loading...
Note Loading...
Set Loading...
S = n = 1 ∑ 9 9 n + n 2 + n 4 n = n = 1 ∑ 9 9 ( n 2 − n + 1 ) ( n 2 + n + 1 ) n = 2 1 n = 1 ∑ 9 9 ( n 2 − n + 1 1 − n 2 + n + 1 1 ) = 2 1 n = 1 ∑ 9 9 ( n 2 − n + 1 1 − ( n + 1 ) 2 − ( n + 1 ) + 1 1 ) = 2 1 ( n = 1 ∑ 9 9 n 2 − n + 1 1 − n = 2 ∑ 1 0 0 n 2 − n + 1 1 ) = 2 1 ( 1 1 − 1 0 0 2 − 1 0 0 + 1 1 ) > 2 1 ( 0 . 9 9 9 9 ) = 0 . 4 9 9 9 5
⟹ 0 . 4 9 < S < 0 . 5 .